THE PROCESS OF FORMING OF COMMON IDENTITY AS THE FACTOR OF EUROPEAN INTEGRATION OF UKRAINE - Кучма, Л.О.; Максимович, К.Ю. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
In the article are considered the prospects of the process of European integration of Ukraine through the process of forming of common identity as the total combination of national identities of separate nations. It is considered the main problems of Ukraine through the theory of “soft” power of Europe in the process of forming of national identity as the basis of common identity. Are analyzed an elements of state program of PR providing of European integration, is indicated the necessary of informing the young people about the basis of European coexistence.